Effects of melatonin treatment on browning alleviation of fresh‐cut foods. Issue 9 (26th May 2021) - Xiao, Yanhui; Xie, Jing; Wu, Chunshuang; He, Jinming; Wang, Bin
Abstract: Enzymatic browning is the main quality issue of fresh‐cut foods. This study investigated the effects of different concentrations (0.05, 0.1, and 0.2 mM) of melatonin (MT) treatment on the enzymatic browning of four fresh‐cut foods, including apples ( Malus domestica ), pears ( Pyrus spp.), potatoes ( Solanum tuberosum ), and taros ( Colocasia esculenta ), and found that only 0.05 mM MT was most significant at enhancing the L* values and reducing the browning index (BI) in all four foods. This suggests that 0.05 mM MT might be a universal concentration for the browning alleviation of fresh‐cut foods. MT treatment increased the total phenolic contents and PAL activities but reduced the activities of POD, PPO, and LOX in fresh‐cut taros. Furthermore, MT significantly affected the expression of sixteen browning‐related genes in fresh‐cut taros during storage. These results suggest that MT reduced fresh‐cut food browning by regulating the activities of browning‐related enzymes. However, MT did not significantly influence the browning degree or PPO activity of the taro mash in vitro, suggesting that MT might regulate enzyme activity in an indirect manner. Overall, these results indicate that MT might be a promising anti‐browning agent to alleviate the browning of fresh‐cut foods. Practical applications: Melatonin (MT) is an endogenously produced indoleamine. Previous studies have reported that MT displays protective activities in many agricultural products. However, the reported protective MT concentrations vary between different products. To extend this agent to the fresh‐cut industry, it is necessary to determine the universal dosage of MT needed for application efficiency. In this study, the effects of three concentrations (0.05, 0.1, and 0.2 mM) of MT on four fresh‐cut foods, including apples, pears, potatoes, and taros, were investigated. The results showed that MT treatment alleviated browning development in the slices of these four foods and that 0.05 mM MT was the most effective treatment. Moreover, 0.05 mM MT significantly affected the activities of browning‐related enzymes. These results suggest that 0.05 mM MT is a universal dosage for reducing surface browning in fresh‐cut foods. This study provides a foundation for the application of MT in the processing of fresh‐cut foods, especially fresh‐cut taros. Abstract : This study demonstrated the preventative effects of melatonin on the browning of fresh‐cut foods. 0.05 mM melatonin was most effective at reducing food browning, suggesting that this dosage was universal for food browning prevention. PAL, POD, PPO and LOX activity and gene expression were significantly affected by melatonin treatment in fresh‐cut taros, suggesting that melatonin reduced food browning by indirectly regulating browning‐related enzymes.